Beyond Contraceptives: Family Planning, Anti-abortionism, and Sexual Education in Paraguay, 1966-1977 - Chesterton, Bridget María (Jahrbuch für Geschichte Lateinamerikas, 2023)
This article studies the Centro Paraguayo de Estudios de la Población (CEPEP) when the organization was led by Dr. Dario Castagnino. It considers his personal and professional reasons in starting the organization. More fundamentally the study considers how anti-abortionism drove the philosophy of the organization to educate the Paraguayan public in various methods of birth control and sexual education. Using oral testimony and the surviving documentation of the organization this article aims to better understand how family planning and sexual education was delivered to an eager public.